Forests in development: A vital balance - Montes, Leopoldo; Schlichter, Tomás (Springer Netherlands, 2012)
Forests in Development: A Vital Balance, shows some of the main advances in forestry over the six years spanning between the XII World Forestry Congress in Canada and the XIII WFC held in Buenos Aires. The book covers most of the themes of the XIII WFC, from biodiversity through production, policies, environmental services, and economic aspects, linked by sustainability. It provides a comprehensive view of forestry today, conveying its different aspects through one solid piece addressed by authors whose work denotes a concept of sustainable forest management which is not so much a puzzle laboriously put together as a many-faced unity, steered to achieve ultimately a better quality of living for present and future generations.